Cloud Computing Implementation In Early Detection of PCOS Disease Application - Lumangkun, Mordekhai Gerine; Anggraeny, Fetty Try (Engineering and Technology International Journal, 2023)
This project aims at healthcare especially for women. This project is an application-based model to predict the risk of someone getting a syndrome called PCOS, based on their condition and will be deployed to Google Cloud. The risk is divided into two categories, which are low and high. After the model successfully classifies the risk, the application will not show the result to the user explicitly, but the application will give some recommendations or health tips according to the risk that has been classified. The results will differ among patients with certain categories and it is generated by chat GPT by OpenAI based on the model classification and the user data. This article will explain the role of Cloud Computing in the development of an early detection application for Polycystic Ovary Syndrome (PCOS) called PCOS Pal.